Development Strategy of The Smallholder Plantation of The Sindang Community in Jukung Village, Lubuklinggau City, South Sumatra - Paisal Ansiska; Jati Batoro; Roedy Soelistyono (Graduate Program, 2017)
Sindang community located in the Jukung village Lubuklinggau city is a community that manages smallholders as their agricultural activities. The plantation sector is a source of livelihood of the people the majority of Sindang community. Plantation management people are still traditional and less intensive farming estates is the weakness of the people in the community that need to be done Sindang Smallholder plantation development strategy. The determination of strategy should be beneficial economic, social, political, cultural, environment. the aim of this study is to determine the factors that influence and provide recommendations and priorities of the people of plantation development strategies Sindang community. The method used is the SWOT analysis and analysis QSPM. The results of this study were 1) the development of Smallholder plantation in Sindang communities affected by internal elements (strengths and weaknesses) and external factors (opportunities and threats). the suitability of a power element is growing and the culture of the smallholders with influence value of 1.08; for the element of weakness is institutional weakness of farmers and the cultivation process less than the maximum value of 2.55 influence. The element of chance is the support of the government and change the culture system to influence the value of 0.87; and the element of threat is the lack of cooperation between the farmer and the source of innovation and poor quality of production with a value of 1.87 influence. 2) Referrals development must focus on the strategy to overcome the weaknesses (internal) and threats (external) are the construction of smallholders with agricultural systems are environmentally friendly, doing planting agricultural crops are more diverse/strengthening of the functions of agricultural land, management of post harvest to give value adding, Conducting training/education about organizational management and farm management.Keyword: Development Strategy, Smallholder Plantation, SWOT